2016
DOI: 10.1002/pbc.25897
|View full text |Cite
|
Sign up to set email alerts
|

Yield of Urinalysis Screening in Pediatric Cancer Survivors

Abstract: Background The Children's Oncology Group (COG) publishes consensus guidelines with screening recommendations for early identification of treatment related morbidities among childhood cancer survivors. We sought to estimate the yield of recommended yearly urinalysis screening for genitourinary complications per Version 3.0 of the COG Long-Term Follow-Up Guidelines and identify possible risk factors for abnormal screening in a survivor population. Procedure A database of pediatric cancer survivors evaluated be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…19 TBI, abdominal radiotherapy >30 Gy, and ifosfamide were associated with albuminuria. The association of TBI and HD ifosfamide with abnormal urinalysis was also observed by Ramirez et al 48 in a cohort of 773 CCS. A novel finding of this study includes exposure to HD-abdominal radiotherapy (>30 Gy) as a risk factor for proteinuria.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…19 TBI, abdominal radiotherapy >30 Gy, and ifosfamide were associated with albuminuria. The association of TBI and HD ifosfamide with abnormal urinalysis was also observed by Ramirez et al 48 in a cohort of 773 CCS. A novel finding of this study includes exposure to HD-abdominal radiotherapy (>30 Gy) as a risk factor for proteinuria.…”
Section: Discussionsupporting
confidence: 75%
“…The prevalence in our study population is the highest to date compared with other large CCS cohorts where proteinuria was observed in 4.8%-14.5%. 10,22,48 This can be a result of more exposure to nephrotoxic agents in our cohort, as well as the longer follow-up period or differences in measurement tools. The high prevalence is worrisome, because even a mildly increased albumin-to-creatinine ratio is associated with a faster GFR decline.…”
Section: Discussionmentioning
confidence: 99%
“…97 In cancer survivors, MA is significantly more prevalent on urine screening than either hematuria or proteinuria. 98…”
Section: Resultsmentioning
confidence: 99%
“…97 In cancer survivors, MA is significantly more prevalent on urine screening than either hematuria or proteinuria. 98 Aminoglycoside antibiotics and antifungals such as amphotericin can cause AKI. 99 Toxic levels of the heavy metals lead, cadmium, uranium, and mercury damage the renal tubules, with resulting nephron loss.…”
Section: Resultsmentioning
confidence: 99%
“…[31] One Cochrane review was found on the topic (updated in 2019) [32]. It identified several studies reporting on associations between RT and kidney-related outcomes such as reduced eGFR, [33][34][35][36][37] proteinuria, [33,34,38] and elevated blood pressure. [12,34,[39][40][41] Most studies did not find significant associations of RT with renal outcomes (category D, see Table 1).…”
Section: Livermentioning
confidence: 99%